2020
DOI: 10.26822/iejee.2020562136
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Writing-With or Without Metacognition : An Exploratory Study of 11- to 12-Year-Old Students Writing A Book Review

Abstract: In this contribution, we attempt to answer two research questions: (1) What effects do metacognitive questions have on students' writing skills? and (2) How do students respond to metacognitive questions? To answer these questions, we conducted an experiment with 43 students who were 11 to 12 years old. They were engaged in writing in a particular genre: book reviews. These pupils belonged to two classes at the same school, and for three weeks they experienced an instructional system combining identified princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
1
12
0
3
Order By: Relevance
“…There is also the question of which modalities are most effective for peers to use in giving feedback to others as part of an oral performance evaluation. In their study, Colognesi et al (2020b) compared two modalities for students to use in giving feedback on their peers' oral performances: written or oral with discussion. While student performance improved significantly for both modalities, students who received negotiated oral feedback received more guidance and made more progress.…”
Section: Revista Da Abralinmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also the question of which modalities are most effective for peers to use in giving feedback to others as part of an oral performance evaluation. In their study, Colognesi et al (2020b) compared two modalities for students to use in giving feedback on their peers' oral performances: written or oral with discussion. While student performance improved significantly for both modalities, students who received negotiated oral feedback received more guidance and made more progress.…”
Section: Revista Da Abralinmentioning
confidence: 99%
“…Thus, the teacher can support students' metacognition at three points: before, during, and after the tasks; in this case, the oral performance tasks. This is done by activating strategies for orientation, planning, monitoring, regulation, and evaluation of the product and the process (COLOGNESI et al, 2020b;EFKLIDES, 2008;VEENMAN, 2012). It is then possible to invite students to verbalize their process, make judgments about their learning, or even take a look at how confident they feel about the tasks (DOUBLE; BIRNEY, 2019).…”
Section: Revista Da Abralinmentioning
confidence: 99%
“…Research has proved that learning metacognitive strategies improve writing skills [1,13,14,16,31,33]. Metacognitive strategies help learners assess their cognitive progress and self-evaluate their writing skill.…”
Section: Metacognitive Strategies and Writing Skillsmentioning
confidence: 99%
“…A large number of studies have concentrated on the critical role of metacognitive knowledge in developing receptive English language skills such as reading and listening [8][9][10][11][12]. Furthermore, some studies have found that developing learners' metacognitive knowledge results in their better performance in writing tasks [1][2][3][13][14][15][16]. Furthermore, in another study, Panggabean and Triassanti [17] found that metacognitive strategy training enhanced the students' oral presentation skill in an EFL class.…”
Section: Introductionmentioning
confidence: 99%
“…Since the last five years, prior studies on writing, which worked on the variables of growth mindsets, self-efficacy, and metacognition, have been conducted, and such studies have been very contributive to us and provided us with adequate knowledge and data about the aforementioned three variables' roles in writing. Nonetheless, those studies seem to have addressed the three variables as single variables in respective studies (Grenner et al, 2021;Howe & Wig, 2017); they have examined the interrelationships of mere two out of the three variables (Colognesi et al, 2020;Vincent et al, 2021); or they have scrutinized the interrelatedness of respective three variables with other variables (Chakma et al, 2021;Puryantoa et al, 2021). However, to the best of our knowledge, no prior studies have been oriented towards conducting an exploratory analysis of the interplay among academic writing growth mindsets, selfefficacy, and metacognition in the context of undergraduate thesis writing as a single study.…”
Section: Introductionmentioning
confidence: 99%